Output tracking control for TRMS based on time receding optimal observation of disturbances - Loc, Dam Bao; Cuong, Nguyen Duy; Phuoc, Nguyen Doan (Vietnam Journal of Science and Technology, 2020)
The paper presents an approach to design the adaptive output tracking controller for disturbed Twin Rotor Multi-Input Multi-Output System (TRMS) by using a time receding observer of functional disturbances for compensative control purpose, without using conventional methods as a neural network. To do this, first the disturbed Euler-Lagrange model of TRMS is converted to an equivalent bilinear form. And then, secondly an optimal disturbances estimator for this disturbed bilinear system is constructed based on time receding minimizing their effect. The complete output tracking controller for TRMS is created then by combining an exact linearization controller with the proposed disturbances estimation mechanism. Simulation results show that the here suggested controller meet completely the expected output tracking performances.